Use of Eisenia fetida as a Biological Risk Marker in a Qualitative Eco Assessment Test of a Romanian Watercourse - Romeo T. Cristina; Mihai Baroga; Eugenia Dumitrescu; Florin Muselin; Alexandru O. Doma; Dan Manea; Ioan Banatean-Dunea (Biology, 2022)
The qualitative trials were conducted by exposing earthworms to diverse contaminants sources using standard earthworms’ avoidance tests (considered useful ab initio indicators). For two years, we observed the Jiu River pollution points. We observed soil traits in 15 sampling points from two neighboring Romanian counties where Jiu River flows, by evaluating the risk of pollution on Eisenia fetida earthworms. The ISO: 11268-2:2015 acute static test was used, following the ethological and bodily features of E. fetida earthworms for 14 days, and then the results obtained for clean soils vs. those presumed polluted were statistically analyzed. Results disclosed statistically significant values (p < 0.05) for the two-way ANOVA and Tukey multiple comparisons tests used for the soil samples thought to be polluted. The mortality percentages by location/replica/year/county find out a high statistical correlation documenting observations related to soil samples gathered from 10 m (p < 0.01) and 30 m (p < 0.001). Compared with the control, the statistical analysis of Relative Growth Rate (RGR) (p < 0.05) and Specific Growth Rate (SGR) (p < 0.01) confirmed that, in the case of soil samples collected from 10 and 30 m from the Jiu River’s axis, the earthworms did not gain weight, qualitatively attesting the pollution suspicion/presence of chemical factors potentially pernicious for earthworms.